Reconstruction and electronic properties of interface between carbon nanotubes and ferromagnetic co electrodes - Cuong, Nguyen Tien; Mohamed, Mohd Ambri; Otsuka, Nobuo; Chi, Dam Hieu (Trans Tech Publications Ltd., Switzerland, 2012)
The reconstruction and electronic structures of the interfaces between single wall carbon nanotubes and ferromagnetic Co electrodes were studied in the framework of density functional theory. The obtained results revealed that there is a strong interaction between carbon nanotubes and Co electrodes. At the interface region, Top layers of Co surface have been significantly reconstructed. The nature of chemical bonds at the Co-C interface is covalent bonding. The increase of the electron density occurs mainly at the interface where a substantial concentration of electron accumulates in Co-C bonds. A small amount of charge transfer from Co electrode to carbon nanotube junction was found. In addition, the spin polarization of Co atoms at the interface region has been suppressed due to the interaction with a carbon nanotube. It implies that the spin transport through this layer is low, which results in the small hysteretic magneto-resistance of carbon nanotube devices.